Curcuminoid EF24 enhances the anti‐tumour activity of Akt inhibitor MK‐2206 through ROS‐mediated endoplasmic reticulum stress and mitochondrial dysfunction in gastric cancer. (6th April 2017) - Chen, Xi; Dai, Xuanxuan; Zou, Peng; Chen, Weiqian; Rajamanickam, Vinothkumar; Feng, Chen; Zhuge, Weishan; Qiu, Chenyu; Ye, Qingqing; Zhang, Xiaohua; Liang, Guang
Abstract : Background and Purpose: Gastric cancer is one of the leading causes of morbidity and mortality worldwide. Akt is an anti‐apoptotic kinase that plays a dynamic role in cell survival and is implicated in the pathogenesis of gastric cancer. MK‐2206, the first allosteric inhibitor of Akt, is in clinical trials for a number of cancers. Although preclinical studies showed promise, clinical trials reported it had no effect when given alone at tolerated doses. The aim of our study was to delineate the effects of MK‐2206 on gastric cancer cells and explore the ability of combination treatments to enhance the anti‐tumour activity of MK‐2206. Experimental Approach: SGC‐7901, BGC‐823 cells and immunodeficient mice were chosen as a model to study the treatment effects. Changes in cell viability, apoptosis and ROS, endoplasmic reticulum stress and mitochondrial dysfunction in the cells were analysed by MTT assays, ROS imaging and FACSCalibur, electron microscopy, JC‐1 staining and western blotting. Key Results: MK‐2206 induced apoptotic cell death through the generation of ROS. We utilized ROS production to target gastric cancer cells by combining MK‐2206 and an ROS inducer EF24. Our in vitro and in vivo xenograft studies showed that combined treatment with MK‐2206 and EF24 synergistically induced apoptosis in gastric cancer cells and caused cell cycle arrest. These activities were mediated through ROS generation and the induction of endoplasmic reticulum stress and mitochondrial dysfunction. Conclusion and Implications: Targeting ROS generation by using a combination of an Akt inhibitor and EF24 could have potential as a therapy for gastric cancer.